Effects of cadmium on uterine contractions in different species in vitro - Kara, H; Servi, K; Akar, Y (Scientific Technical Research Council Turkey, 2003)
The aim of this study was to examine the effects of cadmium on oxytocin-induced myometrium contractions in rats, cows and cats in vitro. The frequency was 12.20 +/- 1.2, 11.25 +/- 2.7 and 10.70 +/- 2.5/10 min, respectively, after 0.01 mM oxytocin induced with myometrial samples in rats, cows and cats. The peak amplitude was 3.84 +/- 0.50, 3.44 +/- 0.65 and 3.35 +/- 0.45 g. respectively, after oxytocin induction. The frequency and peak amplitude decreased after the addition of 0.01 mM cadmium chloride (CdCl2). The frequency was 1.2 +/- 0.4 (p < 0.001), 2.5 +/- 0.5 (p < 0.001) and 2.0 +/- 0.6(p < 0.001), respectively, and the peak amplitude was 0.7 +/- 0.3 (p < 0.001), 1.2 +/- 0.2 (p < 0.001) and 0.8 +/- 0.4 g (p < 0.001), respectively, in rat, cow and cat myometrium. Finally, the myometrium contractions were completely inhibited in the three species. In conclusion, the effects of cadmium may inhibit both calcium channels and the intracellular-induced mechanism.
Farkli türlerde i?n vitro uterus kontraksiyonlari üzerine kadmiyumun etkisi
Keywords: myometrium; contraction; oxytocin; cadmium